Penerapan green economy dalam pembelajaran tematik untuk kemandirian ekonomi pesantren berbasis zero waste - Qamariyah, Siti; Musoffan, Musoffan; Sholeh, Muhammad Shoimus (Penamas: Journal of Community Service, 2025)
Islamic boarding schools (pesantren) play a strategic role in developing individuals who are morally upright and economically independent. However, many pesantren face environmental challenges due to poor waste management. This community service project aimed to implement the green economy concept based on zero waste through thematic learning as a means to enhance the economic independence of pesantren and create a cleaner, healthier environment. The project was conducted at the Sumber Anyar Pamekasan Islamic boarding school, located in the Fatahillah complex, utilizing the ADIED model (Analysis, Design, Implementation, Evaluation, and Development). Activities included socialization, educational training on waste management, hands-on workshops on converting waste into compost and crafts, and evaluation using pre-tests and post-tests. The results showed a significant improvement in participants' understanding, with an N-Gain score of 0.76 (high category). These findings demonstrate that integrating thematic learning with green economy principles is effective in raising environmental awareness while generating economic value. The program contributes to the development of a sustainable, environmentally conscious curriculum and empowers students in Islamic boarding schools.